A comprehensive in vitro and in vivo metabolism study of hydroxysafflor yellow A. (27th November 2017) - Wu, Liang; Tang, Yuping; Shan, Chenxiao; Chai, Chuan; Zhou, Zhu; Shi, Xuqin; Ding, Ning; Wang, Jiaying; Lin, Liping; Tan, Renxiang
Abstract: As the most important marker component in Carthamus tinctorius L., hydroxysafflor yellow A (HSYA) was widely used in the prevention and treatment of cardiovascular diseases, due to its effect of improving blood supply, suppressing oxidative stress, and protecting against ischemia/reperfusion. In this paper, both an in vitro microsomal incubation and an in vivo animal experiment were conducted, along with an LC‐Q‐TOF/MS instrument and a 3‐step protocol, to further explore the metabolism of HSYA. As a result, a total of 10 metabolites were searched and tentatively identified in plasma, urine, and feces after intravenous administration of HSYA to male rats, although no obvious biotransformation was found in the simulated rat liver microsomal system. The metabolites detected involving both phase I and phase II metabolism including dehydration, deglycosylation, methylation, and glucuronic acid conjugation. A few of the metabolites underwent more than one‐step metabolic reactions, and some have not been reported before. The study would contribute to a further understanding of the metabolism of HSYA and provide scientific evidence for its pharmacodynamic mechanism research and clinical use.